2017
DOI: 10.2298/fil1717475a
|View full text |Cite
|
Sign up to set email alerts
|

Fixed point theorems in complete modular metric spaces and an application to anti-periodic boundary value problems

Abstract: In this paper existence and uniqueness of fixed points for a general class of contractive and nonexpansive mappings on modular metric spaces is discussed. As an application of the theoretical results, the existence of a solution of anti-periodic boundary value problems for nonlinear first order differential equations of Carath?odory?s type is considered in the framework of modular metric spaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Following this initial results, a number of authors have reported several fixed point results for certain mappings in modular metric spaces, see e.g. [1,7,10] and related references therein.…”
Section: Introductionmentioning
confidence: 94%
“…Following this initial results, a number of authors have reported several fixed point results for certain mappings in modular metric spaces, see e.g. [1,7,10] and related references therein.…”
Section: Introductionmentioning
confidence: 94%
“…An important role is played by the fixed-point principle to obtain the solvability of various types of operator equations (see, for example, [25][26][27][28][29]). We will apply the following fixed-point theorem to obtain the main results.…”
Section: Preliminariesmentioning
confidence: 99%
“…Firstly, Nakano initiated the concept of modulared spaces [25]. Later, some authors proved new fixed point theorems of Banach type in modular spaces [1,13,16,20,21,32,2,3,5,8,9,10,12,14,19,23,28,29,33]. In this work, we present some fixed point results as a generalization of Banach's fixed point theorem using some convenient constants in the contraction assumption in modular spaces.…”
Section: Introductionmentioning
confidence: 98%